Optimization of Lubrication and Compression Process Parameters of Vitamin C Film-Coated Caplets - Pranasti, Ernestine Arianditha; Utami, Ratna Annisa; Nugraha, Yuda Prasetya (UI Scholars Hub, 2023)
Tablet production is a very intricate process influenced by numerous process variables or parameters. This study aimed to identify the critical processing variables that affect Critical Quality Attributes (CQAs) of vitamin C film-coated caplets utilizing a statistical experimental design. A two-level complete factorial design with two central points was used to examine the process parameters that posed the greatest risk to CQAs. The process variables investigated included mesh size and duration for the lubrication process, as well as speed and main thickness for compression. Statistical results showed that mesh number, lubrication time, and their interaction significantly affect flow rate, Hausner ratio, and compressibility index. Higher mesh number and longer duration improved flow properties; lower main thickness significantly increased core caplet hardness; and lower dissolution rates were observed at higher compression speeds. Based on this study, it can be concluded that mesh number and lubrication time only significantly affected the bulk quality attributes but did not have a significant impact on the quality attributes of vitamin C caplets. On the other hand, the parameters of the compression process, such as speed and main thickness, greatly impacted the quality attributes of vitamin C caplets. In this study, the use of mesh number 20 with 7 minutes of lubrication, and a speed of 17 rpm with a main thickness scale of 2.00 were determined as the optimal process parameters. The optimal process parameters for the lubrication and compression processes were obtained from statistical analysis of the response data.